FACTORS AFFECTING WOMEN SELECTION IN 2019 ELECTION IN BANTUL REGENCY - Dita Winda Hastuti; Dian Eka Rahmawati (POLITICO, 2021)
This study aims to determine how the representation of women in the 2019 elections in Bantul Regency and analyze what are the factors that influence the choice of women in the 2019 elections in Bantul Regency. This type of research is qualitative, with data collection techniques in the form of documentation and interviews. The analysis technique used is data reduction, data presentation, and data verification. Bantul Regency in the representation of women has fulfilled the quota of 30% or more and is precisely inversely proportional to the choice of women who did not reach the 30% quota. Therefore, researchers are interested in making Bantul Regency a case study in this research. The results of this study show that firstly, there was a gap in the number and percentage between women's representation totaling 204 people or equivalent to 46% with the electability of women in the 2019 elections in Bantul Regency only amounting to 4 people or 8.9%. Second, there are additional factors that can be categorized into supporting factors, namely political party support, cadre motivation, family factors, track record, and a lot of basis of mass and inhibiting factors namely incumbent who is re-nominating and money politics.